KINERJA GURU BIMNBINGAN DAN KONSELING DALAM MELAKSANAKAN BIMBINGAN DAN KONSELING DI SMK NEGERI 1 PEKANBARU - Hendriyansyah Hendriyansyah; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the performance of teacher guidance and counseling in carrying out guidance and counseling in schools. This research method uses qualitative research. Subjects in this study were guidance and counseling teachers at school. Research data was obtained through an open questionnaire. The results showed that the program prepared by the teacher guidance and counseling was an annual program, a syllabus of guidance and counseling services and a counseling and guidance service unit. Guidance and counseling programs implemented as much as 125 hours / year or 3 hours / week then when compared with the total obligations of teachers' workload of guidance and counseling are regulated in Permendikbud no. 111 of 2014, as many as 24 hours / week so that it can be concluded that the implementation of the BK program that has been achieved as much as 33%. Obstacles in the implementation of guidance and counseling programs are the absence of class entry hours and the lack of available facilities at school.Key Words: teacher performance guidance and counseling